2018
DOI: 10.32598/ijpcp.24.2.136
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impulsivity, Sensitivity to Reward and Anhedonia in Distinction People With Symptoms of Borderline Personality Disorder From Ordinary People

Abstract: ObjectivesThe aim of this study is to determine the role of impulsivity, sensitivity to reward and also anhedonia in distinction People with symptoms of borderline personality disorder from normal people. Methods This study uses both the descriptive and correlative method. The sampling method was sampling and targeting type. The samples comprised of students from Tabriz University (2016-2017 academic year), initial 200 candidates for screening and subsequent 80 candidates for target sampling. In the first step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of Nikooy Koupas et al's research 14 showed that there was a negative and significant relation between self-observation and addiction tendency among the sources of self-knowledge, and there was a positive relationship between social feedback and social comparison with addiction tendency and also there was a meaningful relationship between affiliation with delinquent peers and addiction tendency. 15 Finally, the counseling approach of selfknowledge sources can be helpful in decreasing the number of addicts and mentioned problems. Thus, the purpose of the present research was to answer the question of whether group counseling in the form of selfknowledge recourses can increase the level of self-expression of addicts.…”
Section: Citation: Mansoori S Mohagheghimentioning
confidence: 99%
“…The results of Nikooy Koupas et al's research 14 showed that there was a negative and significant relation between self-observation and addiction tendency among the sources of self-knowledge, and there was a positive relationship between social feedback and social comparison with addiction tendency and also there was a meaningful relationship between affiliation with delinquent peers and addiction tendency. 15 Finally, the counseling approach of selfknowledge sources can be helpful in decreasing the number of addicts and mentioned problems. Thus, the purpose of the present research was to answer the question of whether group counseling in the form of selfknowledge recourses can increase the level of self-expression of addicts.…”
Section: Citation: Mansoori S Mohagheghimentioning
confidence: 99%
“…These issues have led families and adolescents to face psychological and emotional crises (Gesi et al, 2020). According to Levinger's theory, individuals' reactions to grief vary, and behaviors in response to grief are largely individual and culture-centered (Levinger, 1992) and can differ based on individual differences, for instance, people with different levels of emotional impulsivity may have different reactions to crises (Mahmood Aliloo, Hashemi Nosratabad, & Karimpour Vazifehkhorani, 2018). Impulsivity is understood as the tendency and readiness to express rapid and unplanned reactions to internal and external stimuli, without considering the consequences and outcomes (Moeller et al, 2001).…”
Section: Introductionmentioning
confidence: 99%